Potassium and sodium ions in a potassium channel studied by molecular dynamics simulations. - Biggin, P; Smith, G; Shrivastava, I; Choe, S; Sansom, MS (2001)
We have performed simulations of both a single potassium ion and a single sodium ion within the pore of the bacterial potassium channel KcsA. For both ions there is a dehydration energy barrier at the cytoplasmic mouth suggesting that the crystal structure is a closed conformation of the channel. There is a potential energy barrier for a sodium ion in the selectivity filter that is not seen for potassium. Radial distribution functions for both ions with the carbonyl oxygens of the selectivity filter indicate that sodium may interact more tightly with the filter than does potassium. This suggests that the key to the ion selectivity of KcsA is the greater dehydration energy of Na(+) ions, and helps to explain the block of KcsA by internal Na(+) ions.